Identifikasi dan inkulturasi Islam Berkemajuan dalam kurikulum Al-Islam Kemuhammadiyahan di Muhammadiyah Boarding School - Pajarianto, Hadi (Ta'dibuna: Jurnal Pendidikan Islam, 2023)
Islam Berkemajuan (Progressive Islam) is the characteristic of Muhammadiyah which was started at the 47th Muktamar in Makassar and then completed in the 48th Muktamar in Solo and is practically taught in all Muhammadiyah Schools. This research aims to identify the characteristic of Islam Berkemajuan in MBS' Curriculum and map the inculturation process as well in formal and informal activities at school. This is qualitative research with Discovering Cultural Themes approach. The data analysis was done by ongoing analysis since the data collection was started. The research data were analyzed in three steps which are data reduction, data display, and data serving. The results of this research show five characteristics (al-khasa'ishu al-khamsu) in Islam Berkemajuan, which are based on Tauhid, sourced from al-Qur'an and al-Sunnah, live by ijtihad and tajdid, developing Wasathiyah, and become rahmah to the world, these have been explained in the learning textbooks of MBS both in Junior and Senior high school level. The inculturation strategy is done with the formal curricular program based on the school's program and through extracurricular self-developing activities. Abstrak Islam Berkemajuan menjadi ciri persyarikatan Muhammadiyah yang dimulai pada muktamar ke-47 di Makassar dan disempurnakan pada Muktamar ke-48 di Solo, secara praktis diajarkan pada semua sekolah Muhammadiyah. Tujuan penelitian ini adalah untuk mengidentifikasi karakteristik Islam Berkemajuan pada kurikulum MBS serta memetakan proses inkulturasi pada kegiatan formal dan nonformal di sekolah. Penelitian ini kualitatif dengan pendekatan Discovering Cultural Themes. Analisis data dilakukan secara on-going analysis sejak pengumpulan data dimulai. Data penelitian dianalisis dengan 3 tahapan yakni reduksi data, display data dan penyajian data. Hasil penelitian menunjukkan karakteristik Lima (al-Khasha'ishu al-Khamsu) dalam Islam Berkemajuan, yakni; berlandaskan pada tauhid, bersumber pada al-Qur'an dan al-Sunnah, menghidupkan Ijtihad dan Tajdid, mengembangkan Wasathiyah, dan mewujudkan rahmat bagi seluruh alam, telah di-breakdown dalam buku teks pembelajaran MBS baik di tingkat SMP maupun SMA. Strategi inkulturasi dilakukan dengan program kurikuler secara formal yang ditetapkan berdasarkan program sekolah, serta ekstrakurikuler pada kegiatan pengembangan diri.